2012
DOI: 10.1111/j.1872-034x.2011.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS13 activity may predict the cumulative survival of patients with liver cirrhosis in comparison with the Child‐Turcotte‐Pugh score and the Model for End‐Stage Liver Disease score

Abstract: ADAMTS13:AC concomitantly decreases as the functional liver capacity decreases. This activity may be a useful prognostic marker that is equal or superior to the CTP score and the MELD score to predict not only the short-term prognosis but also the long-term survival of the cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 56 publications
(107 reference statements)
4
50
0
Order By: Relevance
“…A decline in ADAMTS13 levels with increasing severity of liver disease also promotes normal platelet function. 14 Fibrinolysis is also rebalanced in chronic liver disease due to parallel changes in profibrinolytic and antifibrinolytic proteins.…”
Section: Rebalanced Hemostasismentioning
confidence: 99%
“…A decline in ADAMTS13 levels with increasing severity of liver disease also promotes normal platelet function. 14 Fibrinolysis is also rebalanced in chronic liver disease due to parallel changes in profibrinolytic and antifibrinolytic proteins.…”
Section: Rebalanced Hemostasismentioning
confidence: 99%
“…This is particularly true for the vitamin K-dependent procoagulant factors II, VII, IX, and X, as well as for factor V, but also for the vitamin K-dependent anticoagulant factors protein C and protein S, as well as for antithrombin [1 && ]. A marked imbalance between decreased ADAMTS13 activity and increased production of large vWF multimers has been shown to be closely related to functional liver capacity, hepatic encephalopathy, hepatorenal syndrome, and intractable ascites in advanced liver cirrhosis and may be useful to predict long-term survival of cirrhotic patients [3,4]. On the other hand, the activity of the vWF cleaving enzyme ADAMTS13, a metalloprotease exclusively produced in hepatic stellate cells, is reduced in liver cirrhotic patients.…”
Section: Coagulopathy In Liver Dysfunctionmentioning
confidence: 99%
“…Several previous studies have, however, reported conflicting data on a potential functional role of ADAMTS13 in the pathogenesis of liver diseases [reviewed in (12)]. A beneficial effect of ADAMTS13 activity was observed on liver disease severity, and increased ADAMTS13 activity was associated with an improved prognosis of liver cirrhosis (13), alcoholic hepatitis (14) and hepatic veno-occlusive disease (15). In contrast, a detrimental effect of ADAMTS13 was reported on hepatocellular carcinoma risk in patients suffering from chronic liver disease (16).…”
Section: Introductionmentioning
confidence: 99%